The longitudinal shock of two elastic bars with side viscoresistance of the second bar which is semiendless - An, Nguyen Thuc; Anh, Pho Duc; To, Nguyen Dang; Son, Nguyen Hung (Vietnam Journal of Mechanics, 1995)
In this paper authors studied the problem of longitudinal shock of two elastic bars of which the second bar is semiendless and its side resistance is caused by viscos. Where Authors determined the motions U1 (t, x), U2 (t, x) in the bars and shock time of the bars.